1
$\begingroup$

I have a list of relations of the form

x[1] x[2] + y[1] y[2] - z[1] z[2] == 0

and I want Mathematica to simplify certain expressions using these relations. I have been using FullSimplify with assumptions, and I have found that it doesn't work occasionally. For example:

FullSimplify[(a b - e f)/c, Assumptions -> {a b + c d - e f == 0}]

works just fine, and gives the correct answer -d, but for some reason

FullSimplify[(c d - e f)/a, Assumptions -> {a b + c d - e f == 0}]

returns (c d - e f)/a. Any idea why this happens and how to make sure that Mathematica recognizes the second example as -b?

$\endgroup$
1
  • 2
    $\begingroup$ I'd say that Reduce is more appropriate for this sort of thing. For example: Reduce[(c d - e f)/a == y && a b + c d - e f == 0] $\endgroup$ Sep 24 at 9:51
2
$\begingroup$

It is recommended to act another way around. For example, below I use the equation a b + c d - e f == 0 to express one or another parameter in order to then substitute it to the expression under simplification:

sol1 = Solve[a b + c d - e f == 0, c][[1, 1]]
sol2 = Solve[a b + c d - e f == 0, a][[1, 1]]
sol3 = Solve[a b + c d - e f == 0, d][[1, 1]]

(*  c -> (-a b + e f)/d

a -> (-c d + e f)/b

d -> (-a b + e f)/c   *)

Then let us substitute successively these three solutions into the expression under simplification:

Simplify[(c d - e f)/a /. sol1]
Simplify[(c d - e f)/a /. sol2]
Simplify[(c d - e f)/a /. sol3]


(*  -b

-b

-b  *)

Each of these ways is one step longer than your approach with the equation, but they are safer.

As a minor note: FullSimplify is not necessary here. Simplify is enough.

Have fun!

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.